MYOCARDIAL REPERFUSION IN PATIENTS WITH ACUTE ST-SEGMENT ELEVATION MYOCARDIAL INFARCTION IN THE USE OF MANUAL THROMBUS ASPIRATION - A. S. Tereshchenko; G. K. Arutyunyan; E. V. Merkulov; D. M. Kayraliev; A. E. Grossman; A. N. Samko (Вестник рентгенологии и радиологии, 2018)
Objective: to determine the efficiency and safety of manual thrombus aspiration (TA) in patients with acute ST-segment elevation myocardial infarction.Material and methods. The investigation enrolled 200 patients with ST-segment elevation myocardial infarction. According to prehospital therapy, all the patients were divided into life-saving (n = 100) percutaneous coronary intervention (PCI) (lsPCI) and primary (n = 100) PCI (pPCI) groups. After coronary angiography the patients were randomized into manual TA (n = 50) and non-manual TA (n = 50) groups. The endpoints took into consideration myocardial reperfusion and the impact of TA on immediate results and in-hospital prognosis.Results. The pPCI subgroup with TA as compared to the non-TA subgroup more commonly achieved TIMI-3 flow (82 and 54%, respectively; p = 0.003) and myocardial blush grade 3 or 4 (60 and 36%, respectively, p = 0.016). ECG also showed the achievement of the indirect signs of infarct-related artery reperfusion (pPCI + TA, 44%; and pPCI – TA, 76%; p = 0.001). On the contrary, in the lsPCI group, the best antegrade blood flow was recorded in the non-manual TA patients, as shown by both the TIMI scale (48 and 70%, respectively; p = 0.025) and the myocardial blush grade (24 and 50%, respectively, p=0,007). A larger number of patients from the non-TA subgroup were noted to have a decrease in the ST segment, as evidenced by ECG (slPCI + TA, 34% and slPCI – TA, 54%; p = 0.044).Conclusion. According to angiographic and electrocardiographic findings, coronary blood flow effectively restored in the pPCI + TA group while manual TA did not show any advantages over routine PCI in the slPCI group.